Empirical test of the many-wrongs hypothesis reveals weighted averaging of individual routes in pigeon flocks - Takao Sasaki; Naoki Masuda; Richard P. Mann; Dora Biro (iScience, 2022)
Summary: The ‘many-wrongs hypothesis’ predicts that groups improve their decision-making performance by aggregating members’ diverse opinions. Although this has been considered one of the major benefits of collective movement and migration, whether and how multiple inputs are in fact aggregated for superior directional accuracy has not been empirically verified in non-human animals. Here we showed that larger homing pigeon flocks had significantly more efficient (i.e. shorter) homing routes than smaller flocks, consistent with previous findings and with the predictions of the many-wrongs hypothesis. However, detailed analysis showed that flock routes were not simply averages of individual routes, but instead that pigeons that more faithfully recapitulated their routes during individual flights had a proportionally greater influence on their flocks’ routes. We discuss the implications of our results for possible mechanisms of collective learning as well as for the definition of leadership in animals solving navigational tasks collectively.